The Relationship Between Maternal Stress Level and the Development of Children Aged 24-59 Months in Palembang City - Khilda, Rahima; Rosyada, Amrina (Universitas Teuku Umar, 2023)
The toddler period is a golden period where at the age of 0-5 years the growth and development of the toddler's brain increases rapidly. So every family needs to understand this golden age period so that children's growth and development can be achieved optimally. As individuals who are close to children, mothers have an important role in providing stimulation to children during their development. The study aims to examine the relationship between maternal stress levels and the development of children aged 24-59 months in Palembang City. The study is a quantitative analytic study with a cross-sectional approach. This study uses the design of a random sampling cluster with the number of samples of 128 respondents. There are 8 respondents (80%) of mothers with high levels of stress having children with inappropriate development. Stress levels are associated with child development (p-value=0.047; 95% CI=0.999-24.089) and the confounding variable associated with child development are maternal support system (p-value=<0.001; 95% CI=2.280-10.179). Mothers with high stress levels had a risk of having children with inappropriate development 2.182 times greater than mothers with low stress levels after controlling for the variable of support system (95% CI = 0.418 - 11.389).